Effects of Nitrogen Addition on the Drought Susceptibility of the Leymus chinensis Meadow Ecosystem Vary with Drought Duration - Shi, Baoku; Wang, Yunbo; Meng, Bo; Zhong, Shangzhi; Sun, Wei (Frontiers in Plant Science, 2018)
It is not clear yet how extreme drought and nitrogen (N) deposition influence grassland ecosystem functions when they are considered together, especially in complex field conditions. To explore the response of the Leymus chinensis meadow ecosystem to manipulated extreme drought (45 days), N addition and their interaction, we measured leaf photosynthetic characteristics, aboveground phytomass on the community level and ecosystem C exchange in different treatments at the middle and the end of the drought period. The extreme drought treatment decreased the leaf net CO2 assimilation rate and ecosystem C exchange (gross ecosystem productivity, ecosystem respiration and net ecosystem CO2 exchange). In contrast, the N addition treatment increased aboveground phytomass, gross ecosystem productivity and net ecosystem CO2 exchange. The effects of N addition on the drought susceptibility of the L. chinensis meadow ecosystem varied with drought severity. The N addition treatment alleviated drought-induced suppression of CO2 exchange at the leaf and ecosystem levels in the middle of the drought period, whereas it exacerbated drought-induced suppression of the CO2 exchange and aboveground phytomass on the community level at the end of the drought period. Given that dominance by L. chinensis is a characteristic of the studied ecosystem, knowledge of the traits of L. chinensis and its response to multiple global change drivers will be crucial for predicting future ecosystem functions. Furthermore, increasing N deposition may affect the response of the L. chinensis meadow ecosystem to further droughts by increasing carbon allocation to roots and therefore root-shoot ratios.